Influence for Ambient Relative Humidity and Pollution on Infrared Detection of Zero Resistance Insulators - Chen, Ling; Lin, Feng; Chen, Minjiang; Huang, Xiongtao; He, Ruomei; Zheng, Yaqing (Frontiers in Energy Research, 2022)
Porcelain insulators play a vital role for the safety and stability operations of electric systems. In a strong electric field, these insulators easily break down and become zero resistance insulators, which impacts the safety and stability operations of an electric system. As a result, a three-dimensional zero resistance insulator model is set up based on COMSOL. To proceed, first, we studied the voltage and current density law of insulator string when ambient relative humidity, pollution degree, and pollution salt composition are different. Then, the insulator infrared detection test is carried out in an artificial fog chamber. Results showed that the zero resistance insulator has the greatest influence on voltage when it is at a high voltage terminal, and it has the least influence on voltage when it is in the middle position. As the relative range between non-adjacent insulators and zero resistance insulators increases, the implications for a zero resistance insulator on adjacent position insulators will decrease continuously. Farther is the range between different positions on the insulators and the center axis of rotation and lower is the current density and temperature rise. The overall temperature rise of the insulator string gradually increases due to the increase in the relative humidity and pollution degree of the environment. Finally, the results indicate that the temperature difference between zero resistance insulators and other insulators gradually increases and can provide support for the infrared detection of zero resistance insulators.